السؤال الأخلاقي بين أرسطو وابن رشد - الضاهر سليمان; صارم علي (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
يهدف هذا البحث إلى دراسة المسألة الأخلاقية بين الموقف الأرسطي والرشدي. ويتناول بالدراسة والتحليل رأي كل منهما في ثلاث مسائل أساسية وهي: - أصل الأخلاق ومجالها. - نظرية الفضيلة. - أصناف الفضائل وترتيبها. وانطلاقاً من معالجتنا لهذه القضايا سنعمل على تحديد مدى التقارب والاختلاف بين الفيلسوفين بهذا الشأن. وعليه سنحاول تبيان الأثر الأرسطي الأخلاقي في الفضاء الفكري العربي الإسلامي ممثلاً بابن رشد، الذي وظّف فهمه للأخلاق الأرسطية في عملية قراءة وتحليل جمهورية أفلاطون.وفي ضوء ما تقدّم نطرح تساؤلاً مشروعاً: هل كان لابن رشد نظرية مستقلّة في الأخلاق، أم أنّه سار على نهج من سبقوه وبالأخص أرسطو في مقاربته للمسألة الأخلاقية؟ The study of the ethical issue in the Aristotelian attitude and Averroes one is the aim of this research. It also studies and analyzes the point of view of each one of them in three fields which are: The originality of ethics and its field The virtue theory Virtues varieties and arrangements According to our dealing with this case, we work on specifying the degree of similarities and differences between the two philosophers. We try to show the Aristotelian moral effect in the Islamic_ Arab intellectual space represented by Averroes whose understanding of Aristotelian ethics in the process of reading and analyzing Plato Republic. In the light of the above, we have the right to ask whether Averroes has an independent ethical theory or he followed the approach of his predecessors, especially Aristotle in his similarity with his ethical issue.